Enhancing Fisheries through Regional Regulation: Assessing Port Service Levies at Fish Auctions - Busura, Zohrin; Moonti, Roy Marthen; Tumuhulawa, Arifin (Manunggal Halim Jaya, 2023)
In accordance with Gorontalo Province Regional Regulation on Retribution of Fish Auction Place (TPI), the retribution is levied on the use of fish auction place along with facilities and infrastructure provided or organized by Gorontalo Province Regional Government which is called retribution object. The purpose of the study is to determine the effectiveness of the government's implementation of Gorontalo Province Regional Regulation Number 6 of 2018 concerning Port Service Levies on Fish Auction and to determine the impact and efforts taken in the government's implementation of Regional Regulation Number 6 of 2018 concerning Port Service Levies on Fish Auction. The type of research used by researchers is using normative and empirical legal research, which is basically a combination of normative legal approaches with the addition of various empirical elements. In this normative and empirical research method is also about the implementation of normative legal provisions (laws) in action in every certain legal event that occurs in a society. The effectiveness of the implementation of retribution collection shows that port service retribution in Tenda Village, Hulontahlangi Subdistrict is still less effective in retribution collection. There is a discrepancy between what is expected in Regional Regulation Number 6 of 2018 concerning Port Service Levies against Fish Auction Sites. So that the effectiveness of the application of port service levies on service rates at the fish auction site is less effective and efforts in implementing Regional Regulation Number 6 of 2018 concerning Port Service Levies on Fish Auction Sites, which consists of socialization, target achievement, and community participation.